Pesantren dalam Era Digital: Antara Tradisi dan Transformasi - Saini, Mukhamat (Tasamuh: Jurnal Studi Islam, 2024)
It is hoped that this research can contribute to understanding the dynamics of Islamic boarding schools in the digital era and how Islamic boarding schools can remain relevant to current developments without losing their traditional identity. Until now, Islamic boarding schools still adhere to three patterns of education system. The educational patterns or systems in question include traditional, modernist and revivalist Islamic boarding schools. Traditional Islamic boarding schools prioritize four basic concepts as the foundation of education, namely tasamuh, ta'addul, tawazun and tawasut. Modernity Islamic boarding school is a form of modern Islamic boarding school that pays attention to change so that it remains relevant with the times. This research uses a qualitative approach with the library research method, which aims to examine the concept of digital Islamic boarding schools through written sources, including books, scientific articles, research reports and other relevant documents. The main data sources in this research consist of: books discussing technological developments in Islamic boarding schools, the Islamic boarding school education system, and digital transformation in the world of Islamic education. Data collection was carried out by searching literature from various sources, both print and online. The data that has been collected will be analyzed descriptively using the thematic analysis method.